mt tRFs, New Players in MELAS Disease - Meseguer, Salvador; Rubio, Mari-Paz (Frontiers in Physiology, 2022)
MELAS (mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes) is an OXPHOS disease mostly caused by the m.3243A>G mutation in the mitochondrial tRNALeu(UUR) gene. Recently we have showed that the mutation significantly changes the expression pattern of several mitochondrial tRNA-derived small RNAs (mt tsRNAs or mt tRFs) in a cybrid model of MELAS and in fibroblasts from MELAS patients versus control cells. Among them are those derived from mt tRNA LeuUUR containing or not the m.3243A>G mutation (mt 5’-tRF LeuUUR-m.3243A>G and mt 5’-tRF LeuUUR), whose expression levels are respectively increased and decreased in both MELAS cybrids and fibroblasts. Here, we asked whether mt 5’-tRF LeuUUR and mt 5’-tRF LeuUUR-m.3243A>G are biologically relevant and whether these mt tRFs are detected in diverse patient samples. Treatment with a mimic oligonucleotide of mt tRNA LeuUUR fragment (mt 5’-tRF LeuUUR) showed a therapeutic potential since it partially restored mitochondrial respiration in MELAS cybrids. Moreover, these mt tRFs could be detected in biofluids like urine and blood. We also investigated the participation of miRNA pathway components Dicer and Ago2 in the mt-tRFs biogenesis process. We found that Dicer and Ago2 localize in the mitochondria of MELAS cybrids, and that immunoprecipitation of these proteins in cytoplasm and mitochondria fractions revealed an increased mt tRF/mt tRNA ratio in MELAS condition compared to WT. These preliminary results suggest an involvement of Dicer and Ago2 in the mechanism of mt tRF biogenesis and action.